Distribusi Spasial dan Temporal Ikan Bonti-bonti (Paratherina striata Aurich), Endemik di Danau Towuti-Sulawesi Selatan - Nasution, Syahroma Husni (JURNAL BIOLOGI INDONESIA, 2008)
ABSTRACTSpatial and Temporal Distribution of Bonti-bonti (Paratherina striata) an EndemicFish in Towuti Lake, South Sulawesi. Bonti-bonti (Paratherina striata) is an endemicfish species in Towuti and Mahalona Lake. This fish included into vulnerable species. Itshould be protected from decreasing of fish population due to increasing exploitationand habitat quality changes. The objective of this research to study on spatial and temporaldistribution of the fish, as a basic information for its conservation. Samples were collectedfrom May 2006 to April 2007 using experimental gillnet mesh size 0.625, 0.75, 1.0, and1.25 inches at five stations. Fish number and size captured during 15 hours. Waterquality parameters that analyzed were temperature, conductivity, pH, and dissolvedoxygen using water quality checker-Horiba, alkalinity used titration methode, whilewater level and rain fall obtained from PT. Inco. Distribution of fish abundance wasanalyzed with Mann-Whitney non-parametric test. Water quality parameters thatinfluencing fish abundance were analyzed by multivariate analysis. The results show thatthe distribution of bonti-bonti spreading widely starting from lakeside to middle of thelake. The highest abundance of the fish are in inlet with sand, gravel, and stone substrat.Fish size was obtained more various at the inlet station than other stasions and it predictedas main habitat. Water qualitiy parameters of were not factors influencing difference ofspatial distribution but it was influenced by behavior of habitat selection. The highesttemporal distribution of the fish abundance in November and December influenced bydissolved oxygen and high water level.Key words : Spatial and temporal distribution, Paratherina striata, endemic fish, abundance,Towuti Lake